MCC is a centrosomal protein that relocalizes to non-centrosomal apical sites during intestinal cell differentiation - Tomaz, Lucian B. (2023)
The gene mutated in colorectal cancer (MCC) encodes a coiled-coil protein implicated, as its name suggests, in the pathogenesis of hereditary human colon cancer. To date, however, the contributions of MCC to intestinal homeostasis and disease remain unclear. Here, we examine the subcellular localization of MCC, both at the mRNA and protein levels, in the adult intestinal epithelium. Our findings reveal that Mcc transcripts are restricted to proliferating crypt cells, including Lgr5+ stem cells, where the Mcc protein is distinctly associated with the centrosome. Upon intestinal cellular differentiation, Mcc is redeployed to the apical domain of polarized villus cells where non-centrosomal microtubule organizing centers (ncMTOCs) are positioned. Using intestinal organoids, we show that the shuttling of the Mcc protein depends on phosphorylation by casein kinases 1δ and ε, which are critical modulators of WNT signaling. Together, our findings support a role for MCC in establishing and maintaining the cellular architecture of the intestinal epithelium as a component of both the centrosome and ncMTOC.